2018
DOI: 10.1111/jfs.12527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymus daenensis and Satureja hortensis L. essential oils on quality properties of Iranian Doogh

Abstract: Antifungal activity of Thymus daenensis and Satureja hortensis essential oils (EOs) (0, 50, 100, and 150 ppm) were evaluated against Aspergillus fumigatus in vitro and in the Food model system (un‐heat and heat‐treated Doogh) during 21 days. In vitro results showed that minimum inhibitory concentration and minimum fungicidal concentration of T. daenensis and S. hortensis oils were 6.25 and 12.5%, respectively. In un‐heat treated samples, both EOs showed a significant inhibitory effects rather than the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(52 reference statements)
2
9
0
Order By: Relevance
“…However, EO level at 75 ppm was scored good with an overall acceptability score of 7.23 showing better sensory characteristics of the product and also with appropriated viability of L. paracasei as rated by panelists. In accordance with the present results,Sasanian et al (2018) reported the highest acceptability in terms of flavor in treatments with 50 ppm of Thymus daenensis and Satureja hortensis EOs and stated that greater concentrations of EOs cannot be used due to strong aroma which may cause undesirable organoleptic effect. The sensorial properties of the different Ayran samples…”
supporting
confidence: 91%
See 2 more Smart Citations
“…However, EO level at 75 ppm was scored good with an overall acceptability score of 7.23 showing better sensory characteristics of the product and also with appropriated viability of L. paracasei as rated by panelists. In accordance with the present results,Sasanian et al (2018) reported the highest acceptability in terms of flavor in treatments with 50 ppm of Thymus daenensis and Satureja hortensis EOs and stated that greater concentrations of EOs cannot be used due to strong aroma which may cause undesirable organoleptic effect. The sensorial properties of the different Ayran samples…”
supporting
confidence: 91%
“…The essential oils of A. persica Boiss from the Province of Yazd were previously investigated by Mirjalili et al (2006) They showed (Z)-ocimenone (39.6%), ascaridole (16.0%), and α-terpinene (10.0%) as major constituents. According to previous studies, different factors such as geographical location, harvesting time and season, climate, altitude, and other factors could extremely affect the yield and composition of volatile oils of the same species (Nikbakht et al, 2014).…”
Section: Chemical Analysis Of the Artemisia Persica Eomentioning
confidence: 99%
See 1 more Smart Citation
“…These were then added to un-heated doogh samples which, as a result, became significantly capable of inhibiting the growth of Aspergillus fumigates. [4] Moreover, in the mentioned experiment, the maximum inhibitory effect was seen on the 21st day in samples containing 100 and 150 ppm of T. daenensis EO and also in the ones containing 50 ppm of S. hortensis EO on the 15th day. According to previous results reported by Edadi Ebrahimi and Javadi, [36] the aqueous extract of Echinophora platyloba is proved to have inhibitory effects against gas-producing fungi in doogh, and its inhibitory effect is more prominent against yeasts than molds.…”
Section: Antimicrobial Properties Of Dooghmentioning
confidence: 66%
“…Essential oils (EOs) and plant extracts, commonly used for flavoring the doogh, are especially renowned for their antimicrobial and antifungal activities. [4] Their unique properties emanate from phenolic compounds such as thymol, eugenol and carvacrol, while several other of its chemical constituents include linalool, sabinene, menthol, myrcene, and camphene. [5] Oliveria decumbents is a medicinal plant species of the Umbelliferae (or Apiaceae) family, with powerful aromatic exudates.…”
Section: Introductionmentioning
confidence: 99%